Cryptococcus neoformans-Cryptococcus gattii Species Complex: an International Study of Wild-Type Susceptibility Endpoint Distributions and Epidemiological Cutoff Values for Fluconazole, Itraconazole, Posaconazole, and Voriconazole - Espinel-Ingroff, A. (American Society for Microbiology, 2012)
Epidemiological cutoff values (ECVs) for the Cryptococcus neoformans-Cryptococcus gattii species complex versus fluconazole, itraconazole, posaconazole, and voriconazole are not available. We established ECVs for these species and agents based on wild-type (WT) MIC distributions. A total of 2,985 to 5,733 CLSI MICs for C. neoformans (including isolates of molecular type VNI [MICs for 759 to 1,137 isolates] and VNII, VNIII, and VNIV [MICs for 24 to 57 isolates]) and 705 to 975 MICs for C. gattii (including 42 to 260 for VGI, VGII, VGIII, and VGIV isolates) were gathered in 15 to 24 laboratories (Europe, United States, Argentina, Australia, Brazil, Canada, Cuba, India, Mexico, and South Africa) and were aggregated for analysis. Additionally, 220 to 359 MICs measured using CLSI yeast nitrogen base (YNB) medium instead of CLSI RPMI medium for C. neoformans were evaluated. CLSI RPMI medium ECVs for distributions originating from at least three laboratories, which included ≥95% of the modeled WT population, were as follows: fluconazole, 8 μg/ml (VNI, C. gattii nontyped, VGI, VGIIa, and VGIII), 16 μg/ml (C. neoformans nontyped, VNIII, and VGIV), and 32 μg/ml (VGII); itraconazole, 0.25 μg/ml (VNI), 0.5 μg/ml (C. neoformans and C. gattii nontyped and VGI to VGIII), and 1 μg/ml (VGIV); posaconazole, 0.25 μg/ml (C. neoformans nontyped and VNI) and 0.5 μg/ml (C. gattii nontyped and VGI); and voriconazole, 0.12 μg/ml (VNIV), 0.25 μg/ml (C. neoformans and C. gattii nontyped, VNI, VNIII, VGII, and VGIIa,), and 0.5 μg/ml (VGI). The number of laboratories contributing data for other molecular types was too low to ascertain that the differences were due to factors other than assay variation. In the absence of clinical breakpoints, our ECVs may aid in the detection of isolates with acquired resistance mechanisms and should be listed in the revised CLSI M27-A3 and CLSI M27-S3 documents.